Cover Picture: Medicinal Chemistry Aware Database GDBMedChem (Mol. Inf. 8‐9/2019). Issue 8 (21st August 2019) - Awale, Mahendra; Sirockin, Finton; Stiefl, Nikolaus; Reymond, Jean‐Louis
Abstract : The cover picture shows a 3D‐map of GDBMedChem, containing 10 million drug‐like molecules selected from the generated database GDB17 by applying medicinal chemistry rules, projected from the 42‐dimensional MQN chemical space and color‐coded by the number of ring atoms per molecule. The image is rendered with the interactive web‐based 3D data visualization application Faerun (http://fearun.gdb.tools). Fifteen possible landing sites are indicated as white circles, with examples of molecules to be found there. Each of them marks the location of a Sea of Opportunity. Image created by Daniel Probst. More Details can be found in the Full Paper by Mahendra Awale, Finton Sirockin, Nikolaus Stiefl, and Jean‐Louis Reymond, please see DOI: 10.1002/minf.201900031